Unicornuate Uterus With NonCommunicating Functional Rudimentary Horn In Association With VACTERL Spectrum: Case Report (The Review of Diabetic Studies, 2025)
The unicornuate uterus with a non-communicating rudimentary horn (UUNCRH) is one of the least common congenital uterine malformations. It is defined as a “hemiuterus” with adnexa, whose affected contralateral side develops as a vestige of hollow fibromuscular tissue that does not communicate with the main uterine or vaginal cavity, but may retain functional endometrium. Recently, a close relationship has been demonstrated between UUNCRH and other congenital malformations described in the VACTERL spectrum, a set of vertebral, anorectal, cardiovascular, tracheoesophageal, renal, and limb defects. This link has been documented only twice in the world, therefore, we present the first case in America and Ecuador of a 34-year-old patient with a history of congenital vertebral, anorectal, and renal malformations, diagnosed with UUNCRH. This case highlights several inconsistencies regarding the diagnostic protocol applied, because, despite the fact that the patient had previously undergone several imaging studies and gynecological-obstetric surgical procedures, the congenital defect was not identified in time, which emphasizes the importance of including genital anatomical screening in patients with a history of other congenital structural anomalies.